An Optimized Heat Treatment for Bearing Cup Using FEA Analysis - Lahore, D.R.; Kathar, R.A. (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
In automobile field there are number of manufacturing facilities system has different constructive features according to the vehicle‘s driving type which can be front wheel drive, rear wheel drive or four wheel drive. In rear wheel drive system, elements of the system include clutch, transmission system, propeller shaft, joints, differential, drive shafts and wheels. Each element has many different designs and construction properties depending on the brands of vehicles. Drive shaft is used to transmit motion from gear box to differential. The problem identified after critical analysis of the drive shaft assembly. In that bearing cup assembly was getting cracked during assembly operation in universal joint assembly. This was highest rejection, hence it was decided to eliminate bearing cup failure in drive shaft assembly with cost effective solution. It will highlight the methodology adopted for finalizing the solution to this problem by means of the FEA analysis supported by logical reasoning. Various Heat Treatment processes are compared and it was found that the optimum solution which will reduce the failure of bearing cup as well as reduce the overall manufacturing cost.